1999
DOI: 10.1063/1.124324
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and photoluminescence excitation spectroscopy of Er-doped Si prepared by laser ablation

Abstract: Strong room-temperature photoluminescence (PL) peaks of Er3+ (4I13/2→4I15/2) ions at ∼1.535 μm are obtained from Er-doped thin-film Si layers prepared by laser ablation. The Si sample was found to produce optimum photoluminescence peaks at an annealing temperature of about 450 °C. Experimental results also shows that the thermal quenching of the luminescence intensity from 80 K to room temperature is a factor of 2.5 only. PL excitation measurements reveal that the Er luminescence is significantly excited via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Erbium in silicon was another approach used in order to emit light from silicon. Room temperatuie EL and PL has been reported [37,38,39] with EL decreasing linearly in a logarithmic scale at temperatures above 200 K [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Erbium in silicon was another approach used in order to emit light from silicon. Room temperatuie EL and PL has been reported [37,38,39] with EL decreasing linearly in a logarithmic scale at temperatures above 200 K [38].…”
Section: Resultsmentioning
confidence: 99%
“…Again, from the temperature dependence o f the normalised intensity o f the EL at 1.54 pm was observed that for temperatures above 200 K the EL was decreasing linearly in a logarithmic scale with the decrease o f 1/T. Room-temperature PL at 1.535 pm was obtained from W. L. Ng et al [39] from Er-doped thin-film Si layers prepared by laser ablation and annealed at 450 °C. It was revealed from the PL measurements that the Er luminescence is significantly excited via the silicon band edge.…”
Section: Erbium In Siliconmentioning
confidence: 99%
“…Since the discovery [1][2][3] of luminescent feature, study of dislocation engineered (DE) Si is one of the interesting scientific topics. Distinct from bulk Si, luminescence intensity of DE Si is found to increase with increasing the temperature from low to T=300 K. Here the strain field around dislocations plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Various techniques such as ion implantation, metalorganic chemical vapor deposition, and molecular beam epitaxy have been employed to fabricate Si:Er films. 4 Even though it is not clear which method would produce the optimum material for the highest luminescence efficiency as yet, it has been generally accepted that the Er concentration should be as high as possible without precipitation and the addition of impurities such as oxygen or carbon can enhance the activation of Er and reduce the thermal quenching effect. 4 In addition, the characteristics of the host materials such as crystallinity and band gap as well as the postannealing temperature turned out to play an important role in the emission of 1.54 m light.…”
mentioning
confidence: 99%
“…4 -6 Recently, several groups have reported growth of Erdoped Si films by laser ablation technique. 4,[7][8][9] One of the most prominent advantages of laser ablation over other techniques is the convenient and precise control of Er concentration in the film just by varying the target composition. Also, codoping of oxygen that increases the density of optically active Er via formation of Er-O complexes can be achieved by laser ablation of a single solid target composed of Si, Er, and O.…”
mentioning
confidence: 99%